Securitization without risk transfer - Acharya, Viral V.; Schnabl, Philipp; Suarez, Gustavo (Journal of Financial Economics, 2013)
We analyze asset-backed commercial paper conduits, which experienced a shadow-banking run and played a central role in the early phase of the financial crisis of 2007–2009. We document that commercial banks set up conduits to securitize assets worth $1.3 trillion while insuring the newly securitized assets using explicit guarantees. We show that regulatory arbitrage was an important motive behind setting up conduits. In particular, the guarantees were structured so as to reduce regulatory capital requirements, more so by banks with less capital, and while still providing recourse to bank balance sheets for outside investors. Consistent with such recourse, we find that conduits provided little risk transfer during the run, as losses from conduits remained with banks instead of outside investors and banks with more exposure to conduits had lower stock returns.